2017
DOI: 10.1002/bit.26302
|View full text |Cite
|
Sign up to set email alerts
|

Development of rapid bioconversion with integrated recycle technology for ethanol production from extractive ammonia pretreated corn stover

Abstract: High enzyme loading and low productivity are two major issues impeding low cost ethanol production from lignocellulosic biomass. This work applied rapid bioconversion with integrated recycle technology (RaBIT) and extractive ammonia (EA) pretreatment for conversion of corn stover (CS) to ethanol at high solids loading. Enzymes were recycled via recycling unhydrolyzed solids. Enzymatic hydrolysis with recycled enzymes and fermentation with recycled yeast cells were studied. Both enzymatic hydrolysis time and fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…7 Currently they applied this technology to EA-pretreated (extractive-ammonia-pretreated) corn stover, and the enzyme loading was reduced by 30% to 8.4 mg EP/g cellulose while maintaining a 40 g/L ethanol concentration. 13 To our knowledge, the result obtained in this study was the lowest cellulase dosage (3.3 mg EP/g cellulose) that can reach an a Ethanol yield was calculated on the basis of the theoretical ethanol yield produced from the cellulose in DCCR (Zhang and Bao, 2012).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…7 Currently they applied this technology to EA-pretreated (extractive-ammonia-pretreated) corn stover, and the enzyme loading was reduced by 30% to 8.4 mg EP/g cellulose while maintaining a 40 g/L ethanol concentration. 13 To our knowledge, the result obtained in this study was the lowest cellulase dosage (3.3 mg EP/g cellulose) that can reach an a Ethanol yield was calculated on the basis of the theoretical ethanol yield produced from the cellulose in DCCR (Zhang and Bao, 2012).…”
Section: ■ Results and Discussionmentioning
confidence: 95%
“…9 Partial enzymes reversibly bound to unhydrolyzed solid (UHS) residues could be recycled by removing the liquid hydrolysate and adding fresh substrates for a subsequent batch of hydrolysis. 10,11,13 Cellulase could also be recycled by reusing a small amount of SSF broth, but xylose and lignin accumulation will cause a negative effect on the next round of SSF. 6 Recycling the cellulase present in the stillage requires vacuum distillation conducted at low temperatures (below 55 °C) to avoid denaturing the cellulase activity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often, remaining enzymes will destabilize a bioproduct, if not removed or captured. Likewise, recycling the enzyme can facilitate production and can reduce the cost of biotechnological processes . So, there is a need for capturing, packaging, protecting, and releasing proteins.…”
Section: Introductionmentioning
confidence: 99%
“…After high solid loading, especially in conjunction with hydrolysis following high solid pretreatment, the high the concentration of reducing sugars, the high the ethanol concentration and, thus, it led to the low the bioethanol purification cost, reduced the economic cost of the fermentation or facilities, and the simplified process [21]. Dr. Jin group in Nanjing confirmed that high solids loadings (> 18, wt%) process in enzymatic hydrolysis and fermentation result in high bioethanol production at a low cost [22]. Jin group has integrated ethanol production and fermentation process including dilute alkali or acid pretreatment, substrate mixture ratios and solids loadings from mixtures of corn and corn stover, which are as very rich resources as lignocellulosic feedstocks in China [23,24].…”
mentioning
confidence: 99%